2008
DOI: 10.1002/pola.23132
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of free radical copolymerization behavior and copolymer properties with the strength of π‐π stacking interactions between aromatic fluorocarbons and aromatic hydrocarbons: Comparison of the copolymerization behavior of 2,3,4,5,6‐pentafluorostyrene with styrene, 1‐vinylnaphthalene and 2‐vinylnaphthalene

Abstract: Abstract2,3,4,5,6‐Pentafluorostyrene (PFS) was copolymerized with 1‐vinylnaphathalene (1VN) in bulk by radical copolymerization at 25 °C (r1VNrPFS = 0.070) using t‐butylperoxy pivalate as the inititator, at 70 °C (r1VNrPFS = 0.11) using benzyol peroxide as the initiator, and at 120 °C (r1VNrPFS = 0.28) using t‐butyl peroxide as the initiator; PFS was also copolymerized with 2‐vinylnaphathalene (2VN) in bulk by radical copolymerization at 70 °C (r2VNrPFS = 0.15) under similar conditions. Their reactivity ratios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Since stacking interactions between monomers can play a role in the degree of control over the monomer sequence through preorganization, 9,19,21 the influence of the solvent on both the degree of alternation and the control over molecular weight was investigated. Besides in 1,4-dioxane, the copolymerizations were also performed in N,N-dimethylformamide (DMF) and toluene.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since stacking interactions between monomers can play a role in the degree of control over the monomer sequence through preorganization, 9,19,21 the influence of the solvent on both the degree of alternation and the control over molecular weight was investigated. Besides in 1,4-dioxane, the copolymerizations were also performed in N,N-dimethylformamide (DMF) and toluene.…”
Section: Resultsmentioning
confidence: 99%
“…Size-exclusion chromatography (SEC) analyses were carried out using a Shimadzu pump and Shimadzu UV and RI detectors with tetrahydrofuran (THF) as the eluent and a set of Polymer Standards columns (AM GPC gel, 10 mm, precolumn, 300 Å, and linear mixed bed). The flow rate used for all measurements was 1 mL min 21 . Commercially available PS standards were used for calibration.…”
Section: Redox Initiated Raft Copolymerizations In Bulkmentioning
confidence: 99%
“…As an example of exploiting these interactions, the free radical polymerization of styrene (S) and pentafluorostyrene (PFS) has been reported by Pugh et al to produce an alternating copolymer, attributed to pi–pi stacking between the two different monomeric units. The same group has also reported that copolymers consisting of PFS and vinylnaphthalene possess the same alternating configurations of monomeric units along the backbone, presumably for the same reason . In another study, Weck et al reported the RAFT copolymerization of S and its para‐substituted derivatives with PFS, and found an inclination of the monomers to alternate that coincided with the electron donating ability of the para substituent on the S derivative …”
Section: Introductionmentioning
confidence: 92%
“…There are two types of face‐to‐face interactions that can occur: a sandwich configuration and a parallel, displaced configuration. Of the two, the displaced configuration is slightly preferred due to greater binding energy as a result of smaller inter‐planar distance between the benzene and the HFB . This attraction has a short lifetime, with molecular dynamics simulations estimating it to be between 33 ps at 126 K and 17 ps at 158 K .…”
Section: Introductionmentioning
confidence: 99%
“…139 Moreover, the p-p stacking behavior of copolymers composed of pentafluorostyrene (PFS) and N3 or N4, respectively, was examined by the group of Pugh. 140 So far, polymers based on polymerizable naphthalenes were applied in mixed ligand monolith capillary column material. 141 The composition (including octadecyl acrylate (ODA), N2 and trimethylolpropane trimethacrylate (TRIM) crosslinker) of the column material was altered.…”
Section: Polymerizable Aromatic Dyesmentioning
confidence: 99%